Differences in gripping configurations during the execution of throwing techniques between male and female cadets at the European Judo Championship - Kajmovic, H.; Rado, I.; Mekic, A.; Crnogorac, B.; Colakhodzic, E. (Archives of Budo, 2014)
Background and Study Aim: Gripping (kumi kata) constitutes a very important segment of judo fights and fist contact in said fights, based on which the opponent is controlled and dominated during the fight. The goal of this research is the knowledge about differences in gripping configurations between male and female cadets during the execution of throws at a competition. Material and Methods: The analysis included 470 gripping configurations of male cadets and 350 gripping configurations of female cadets at the 2008 European Judo Championship, held in Sarajevo. For the purpose of establishing differences in frequencies, a Chi-square test with a statistical significance of p=0.05 was used. Results: By analyzing the application of different gripping configurations during the execution of throws among male and female cadets, statistically important differences were identified (p<0.05). Male cadets dominate in the same grip and sleeve end grip, whereas female cadets dominate in the opposite gripping configuration. Sukui nage is the most frequent technique in the case of male cadets, from the same, 11,3% and opposite grip, 6,0%, and in the case of female cadets, from the same grip, 6,0%. The ippon seoi nage throw technique is a technique that was mostly used by both groups (6,4% - 5,4%) in the case of the sleeve end grip, whereas the o uchi gari technique 6,3% was mostly used by female cadets in the opposite grip. Conclusions: A well-developed effort to establish a grip may be one of the key factors in the final results of the fight. By learning the different configurations of grips and techniques that can be applied, the contestants have better possibilities of succeeding in competitions.